A comparison of national open data policies: lessons learned. Issue 3 (17th August 2015) - Nugroho, Rininta Putri; Zuiderwijk, Anneke; Janssen, Marijn; de Jong, Martin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to provide a comprehensive cross-national comparative framework to compare open data policies from different countries and to derive lessons for developing open data policies. Open data policies guide the opening and stimulate the usage of public data. However, some countries have no or less developed open data policies, in this way missing the opportunity to reap the benefits of open data. Design/methodology/approach – Literature review and case studies were conducted to extend an existing comparison framework, and the framework was used to compare open data policies of the UK, the USA, The Netherlands, Kenya and Indonesia. Findings – The comparison of open data policies highlighted several lessons that can be learned, including actions regarding a robust legal framework, generic operational policies, data providers and data users, data quality, designated agencies or taskforces and initiatives and incentives for stimulating demand for data. National policies should also be focused on removing barriers on the operational level and policies for stimulating the release and use of data. Research limitations/implications – There is hardly any research systematically comparing open data policies. The comparative framework provided in this paper is a first analytical basis for cross-national comparison of open data policies and offers possibilities for systematic cross-national lesson-drawing. Practical implications – The authors found two waves of policy-making. The first wave of policy is focused on stimulating the release of data, whereas the second wave of policy is aimed at stimulating use. The comparison can be used to learn from other policies and help to improve open data policies. A third wave of open data policy is expected to materialize focusing on realizing added value from utilizing open data. Social implications – Improving a country's open data policy can help the country to reap the benefits of open data, such as government transparency, efficiency and economic growth. Originality/value – Open data are a recent phenomenon and countries are looking for ways to obtain the benefits. This research can be used for developing and evaluating open data policies.